Financing patterns of innovative SMEs and the perception of innovation barriers in Germany - Heike Belitz; Anna Lejpras (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
We analyze the role of public support in the financing pattern of R&D in German SMEs and their assessment of financing conditions in the context of other framework conditions for innovation. In Germany, there is a diversity of overall well-funded technology-neutral and technology-specific programs providing grants to R&D and innovation projects. Different types of SMEs access public funding for R&D and innovation activities to varying degrees. Using an extensive sample of 2,700 German SMEs that participated in public R&D promotion programs during the 2005-2010 period, we identify four groups of companies with different patterns of public and private sources of R&D finance, such as own capital, grants, private and subsidized loans. The firms in our sample are generally positive about public financing of R&D in Germany in 2010. Despite the different funding patterns, we find only slight variations in this assessment across the four groups of subsidized SMEs. Nevertheless, medium-sized R&D companies (often with external equity investment) that have to finance the market introduction of innovations without a track record, appear to suffer from deficiencies in the provision of loans. Further, the companies perceive obstacles to innovation primarily in the non-financial sphere, namely the supply of skilled personnel, market regulation and competition conditions. Therefore, future work on innovation policies for SMEs should put greater emphasis on the non-financial external framework conditions for firm R&D and innovative activities.
Keywords: O14; O25; O38; L20; 330; R&D promotion; Financing of R&D; Small and medium sized enterprises; Barriers to innovation